Heart failure guidelines and prescribing in primary care across Europe - Hobbs FD Richard; Swedberg Karl; van Gilst Wiek H; Sturm Heidrun B; Haaijer-Ruskamp Flora M (BMC, 2005)
Abstract Background Major international differences in heart failure treatment have been repeatedly described, but the reasons for these differences remain unclear. National guideline recommendations might be a relevant factor. This study, therefore, explored variation of heart failure guideline recommendations in Europe. Methods Treatment recommendations of 14 national guidelines published after 1994 were analyzed in relation to the heart failure treatment guideline of the European Society of Cardiology. To test potential relations between recommendations and prescribing, national prescribing patterns as obtained by a European study in primary care (IMPROVEMENT-HF) were related to selected recommendations in those countries. Results Besides the 14 national guidelines used by primary care physicians in the countries contacted, the European guideline was used in four countries, and separate guidelines for specialists and primary care were available in another four countries. Two countries indicated that no guideline was used up to 2000. Comprehensiveness of the guidelines varied with respect to length, literature included and evidence ratings. Relevant differences in treatment recommendations were seen only in drug classes where evidence had changed recently (β-blockers and spironolactone). The relation between recommendation and prescribing for selected recommendations was inconsistent among countries. Conclusion Differences in guideline recommendations are not sufficient to explain variation of prescribing among countries, thus other factors must be considered.